Bypass of Senescence, Immortalization, and Transformation of Human Hematopoietic Progenitor Cells - Akimov, Sergey S. (2005)
We attempted to extend the lifespan of CD34(+) stem/progenitor cells in human cord blood (CB) by transduction with entiviral vectors carrying the human telomerase catalytic subunit (hTERT) and/or the human papillomavirus type 16 (HPV16) E6 and E7 oncogenes. We found that hTERT was incapable of prolonging the replicative capacity of CB cells maintained under serum-free conditions in the presence of stem cell factor, Flt3 ligand, thrombopoietin, and inter-leukin-3 beyond 4 months (n = 3). However, transduced CB cells cultured in the same cytokine cocktail constitutively expressing HPV16 E6/E7 alone (n = 2) or in concert with hTERT (n = 9) continued to proliferate, giving rise to permanent (>2 years) cell lines with a CD45(+)CD34(-)CD133(+/-)CD44(+)CD235a(+)CD71(+)CD203(+)CD33(+)CD13(+) myeloerythroid/mast cell progenitor phenotype. Notably, CB cell cultures expressing only HPV16 E6/E7 went through a crisis period, and the resulting oligoclonal cell lines were highly aneuploid. By comparison, the CB cell lines obtained by coexpression of HPV16 E6/E7 plus hTERT exhibited near-diploid karyotypes with minimal chromosomal aberrations, concomitant with stabilization of telomere length, yet were clonally derived. The immortalized E6/E7 plus hTERT—expressing CB cells were not tumorigenic when injected intravenously or subcutaneously into sublethally irradiated immunodeficient nonobese diabetic/severe combined immunodeficient mice but could be converted to a malignant state by ectopic expression of a v-H-ras or BCR-ABL oncogene. These findings provide new insights into the mechanisms governing the senescence checkpoint of primitive human hematopoietic precursors and establish a paradigm for studies of the multistep process of human leukemogenesis.